Cost minimization analysis of catheter ablation for paroxysmal atrial fibrillation by catheter technology. (10th January 2019) - Osorio, Jose; Imhoff, Ryan J; Mallow, Peter J; Hunter, Tina D; Goldstein, Laura; Rajendra, Anil; Morales, Gustavo
Aim: Compare the 1-year costs of three catheter ablation technologies for the treatment of paroxysmal atrial fibrillation (PAF).Materials & methods: A decision tree model was developed to estimate 1-year hospital costs associated with an index and potential repeat PAF ablation procedure using the Thermocool ® Smarttouch ® Catheter (ST), Thermocool SF Catheter (SF) or Arctic Front Advance Cryoballoon (CB). Model parameters were estimated using the results of two recently published studies.Results: The ST resulted in average per-patient savings for combined inpatient and outpatient populations of US1488 and US4494 compared with SF and CB, respectively. These cost savings were greater in the inpatient setting.Conclusion: The 1-year expected hospital visit costs for PAF ablation were lower with ST than with SF or CB.